ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA ARITMATIKA SOSIAL KELAS VII - Anggun Shafira Sugondo; Martin Bernard (IKIP Siliwangi, 2021)
The method used in this reserach is descriptive qualitative research which intends to examine the mistakes made by studens when working on social aritmhetic story problems. The data collection technique used Google forms and the subjects of this study were students of class VIII-A junior high school of Mahardhika Batujajar, West Bandung Regency, totaling 22 people. This study uses a written test consisting of five essay questions that have been tested for validity, reliability, discriminating power and difficulty. After that, the data was processed using Microsoft Excel to process test results and calculate the level of errors made by srudents. The results of the calculations are then analyzed, which is then described by the students’ errors in each number of questions. The highest percentage of errors is found in the indicator of question number 2, which is 77,2%, while the lowest percentage of errors is found in the indicator of question number 4, which is 18,1%. Based on the results of the study, it showed that there were several student errors in solving social arithmetic story problems, including errors in writing calculations, understanding the material or describing information on questions and concepts in the material given.